Lead through anything : harness purpose, vitality, and agility to thrive in the face of unrelenting change - Seale, Dustin; Manfre, Ed (McGraw Hill, 2024)
"In today's world of near-constant disruption, every leader faces a slew of conflicting demands involving employees of different generations, cultures, and age groups; one of history's tightest labor markets; and never-ending geopolitical, climate, financial, and health challenges. Lead Through Anything provides simple, tested and actionable strategies to help you continually level-up your impact as an individual, manager, and leader. It walks you through the process of developing a leadership mentality that balances three key elements to achieve sustainable success: Purpose: Create and share a vision that motivates collective achievements and aspirations Vitality: Generate a high level of connection and trust within your teams and organization Agility: Inspire and empower yourself and others to continuously learn and improve Lead Through Anything focuses on a wide variety of skills, such as aligning people and energy to a common cause, building effective teams and helping them work together more selflessly, establishing positive confidence more often in oneself and others, increasing engagement and retaining top talent, and shaping a positive, impact-driven organizational culture"--